Platelet-Rich Plasma Augmentation to Microfracture Provides a Limited Benefit for the Treatment of Cartilage Lesions: A Meta-analysis. Issue 4 (1st April 2020) - Boffa, Angelo; Previtali, Davide; Altamura, Sante Alessandro; Zaffagnini, Stefano; Candrian, Christian; Filardo, Giuseppe
Background: Microfracture is the most common first-line option for the treatment of small chondral lesions, although increasing evidence shows that the clinical benefit of microfracture decreases over time. Platelet-rich plasma (PRP) has been suggested as an effective biological augmentation to improve clinical outcomes after microfracture. Purpose: To evaluate the clinical evidence regarding the application of PRP, documenting safety and efficacy of this augmentation technique to improve microfracture for the treatment of cartilage lesions. Study Design: Systematic review; Level of evidence, 3. Methods: A systematic review was performed in PubMed, EBSCOhost database, and the Cochrane Library to identify comparative studies evaluating the clinical efficacy of PRP augmentation to microfracture. A meta-analysis was performed on articles that reported results for visual analog scale (VAS) for pain, International Knee Documentation Committee (IKDC), and American Orthopaedic Foot and Ankle Society (AOFAS) scores. Risk of bias was documented through use of the Cochrane Collaboration Risk of Bias 2.0 and Risk of Bias in Non-randomized Studies of Interventions assessment tools. The quality assessment was performed according to the Grading of Recommendations Assessment, Development and Evaluation guidelines. Results: A total of 7 studies met the inclusion criteria and were included in the meta-analysis: 4 randomized controlled trials, 2 prospective comparative studies, and 1 retrospective comparative study, for a total of 234 patients. Of the 7 studies included, 4 studies evaluated the effects of PRP treatment in the knee, and 3 studies evaluated effects in the ankle. The analysis of all scores showed a difference favoring PRP treatment in knees (VAS, P = .002 and P < .001 at 12 and 24 months, respectively; IKDC, P < .001 at both follow-up points) and ankles (both VAS and AOFAS, P < .001 at 12 months). The improvement offered by PRP did not reach the minimal clinically important difference (MCID). Conclusion: PRP provided an improvement to microfracture in knees and ankles at short-term follow-up. However, this improvement did not reach the MCID, and thus it was not clinically perceivable by the patients. Moreover, the overall low evidence and the paucity of high-level studies indicate further research is needed to confirm the potential of PRP augmentation to microfracture for the treatment of cartilage lesions.